2005
DOI: 10.1007/s10482-005-3368-2
|View full text |Cite
|
Sign up to set email alerts
|

Screening of cry2 genes in Bacillus thuringiensis isolates from Argentina

Abstract: A polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method for identification of cry2 genes from Bacillus thuringiensis (Bt) was established. Strains from different sources of Argentina were analyzed to study the distribution of cry2 genes. The results showed that cry2Aa/cry2Ab profile was the most abundant irrespective of source and represented 56 of 59 Bt isolates (94.9%). Three different cry2 profiles were found in this collection, one of which was novel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 11 publications
3
19
2
Order By: Relevance
“…1). The combination of cry2Aa/cry2Ab genes were the most frequent, followed by cry2Aa and cry2Ab alone, and a novel cry2-type gene alone was only in JF19-2 (Table 1), which was conformed to the distribution features of Argentina (19). But Ben-Dov et al (3) found that Bt isolates from Israel, Kazakhstan and Uzbekistan containing cry2Ab alone were the most frequent, followed by cry2Aa/cry2Ab and cry2Ab/cry2Ac, which revealed that the distribution of cry2 genes in Sichuan basin was unique compare with other countries of Asian.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…1). The combination of cry2Aa/cry2Ab genes were the most frequent, followed by cry2Aa and cry2Ab alone, and a novel cry2-type gene alone was only in JF19-2 (Table 1), which was conformed to the distribution features of Argentina (19). But Ben-Dov et al (3) found that Bt isolates from Israel, Kazakhstan and Uzbekistan containing cry2Ab alone were the most frequent, followed by cry2Aa/cry2Ab and cry2Ab/cry2Ac, which revealed that the distribution of cry2 genes in Sichuan basin was unique compare with other countries of Asian.…”
Section: Discussionsupporting
confidence: 56%
“…2B), which suggests that these strains may be promising Bt resource for the controlling of pests. Specially, we detected the insecticidal crystal protein genes harbored in strain JF19-2 by using all the primers based on the conserved regions of each class of cry and cyt genes as previously described by Sauka et al (19) and Su (22). But only one PCR product about 1.5 kb was obtained using the primers II (+)/II (-) (data not shown), which revealed that this strain may contain only one cry2 gene.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In order to determine if toxic B. thuringiensis strains posses new cry-type genes, genomic DNA of the strains was amplified with cry2A forward and cry2A reverse universal primers as described by Sauka et al (2005). This primer pair results in a PCR product at around 1556 bp.…”
Section: Partial Dna Sequence Analysis For Cry2 Gene Of Toxic Bacillumentioning
confidence: 99%